PENYISIHAN LOGAM BERAT DARI LIMBAH CAIR LABORATORIUM DENGAN METODE PRESIPITASI DAN ADSORPS - Suprihatin, Suprihatin; Indrasti, Nastiti Siswi (Makara Journal of Science, 2010)
Removal of Heavy Metals from Liquid Laboratory Waste Using Precipitation and Adsorption Methods. Liquid laboratory waste (such as residue of chemical oxygen demand/COD analysis) contains high concentration of heavy metals (mercury/Hg, silver/Ag and chrome/Cr) and has a high potential to pollute the environment. The liquid waste generated by laboratories is generally in small quantity, but it is extremely toxic. It is urgently in need to find out an appropriate method to reduce the problems according to the liquid waste characteristics. In this research work, precipitation and adsorption methods were evaluated to remove Hg, Ag, and Cr from liquid laboratory waste, covering determination of optimum process conditions, levels of removal and achievable treated waste quality. Results showed that a Cr removal of 97% was obtained by pH 10, and Hg and Ag removals of 97-99% were reached by pH 12. Although heavy metals removals using precipitation was very significant, but the concentration of heavy metals in the treated waste was still high (0.73-2.62 mg/L) and need for further treatment. Applying activated carbon adsorption for further treatment of the effluent reduced dissolved heavy metals to 0-0.05 mg/L, depending on the type of heavy metals as well as the type and dosing of activated carbon.